Wait time management strategies at centralized intake system for hip and knee replacement surgery: A need for a blended evidence-based and patient-centered approach. Issue 4 (December 2022) - Marshall, Deborah A.; Bischak, Diane P.; Zaerpour, Farzad; Sharif, Behnam; Smith, Christopher; Reczek, Tanya; Robert, Jill; Werle, Jason; Dick, Donald
Abstract: Objectives: Delays in access to specialty care and elective hip and knee total joint replacement (TJR) surgery remain a major concern among patients with osteoarthritis (OA) in Canada. Centralized intake systems as a wait time management strategy in the face of resource constraints can increase access and patient flow through the system but are not standard practice. We examine how wait time management strategies for the assessment and triaging referrals in a centralized intake system can inform quality improvement initiatives. Design: We developed a discrete-event simulation model using all referrals to the Edmonton Bone and Joint Centre centralized intake system from 2012 to 2016 for the base case model. We assessed the combined effect of three wait time management strategies: improved prioritization, improved sorting through screening, and increased conservative management. Outcomes were measured in terms of patient flow and wait times. Results: The screener sees more patient referrals (7094 compared to 6922), and the number of patients who proceed to surgery is reduced by 282 patients (4%) in the wait time management scenario compared to the base case model. Wait times from referral to surgery are reduced by 54 days for surgical patients. Furthermore, urgent surgical patients experienced lower wait times in all stages of care than non-urgent patients, with wait times from referral to surgery reduced by 86 days. Conclusions: Triaging processes addressing prioritization, screening and conservative management of non-surgical patients can improve patient flow and significantly reduce patient wait times in a centralized intake process for TJR.